Unveiling rural energy pattern determinants: insights from forest-dwelling rural households in the Zagros Mountains, Iran - Bazgir, Ahmad; Maleknia, Rahim; Rahimian, Mehdi (Frontiers in Forests and Global Change, 2024)
This study examines the determinants of energy sources among rural households in the forested regions of the Zagros Mountains in Iran. The research focuses on 157 forest villages, categorized into three groups based on their access to different fuel sources: wood, kerosene and liquefied petroleum gas (LPG), and natural gas (NG). A survey was conducted among 346 rural households using a multi-stage stratified random sampling approach and a questionnaire. The findings reveal that firewood plays a significant role in household energy patterns, particularly in remote areas. Income is identified as a crucial determinant of energy structure, but non-income socio-economic factors also strongly influence energy patterns. Moreover, commercial energy sources exhibit higher energy efficiency, resulting in reduced annual energy consumption compared to the use of firewood as the primary fuel. The study emphasizes the urgent need to address the reliance on low-efficiency energy sources to mitigate deforestation risks. In countries like Iran, where forest resources are limited, transitioning from firewood to higher efficiency fuels becomes imperative for forest conservation and sustainability. The implications of this research underscore the importance of considering both economic and social dimensions in energy planning and interventions, promoting accessible and affordable alternatives to traditional biomass fuels, and designing targeted policies to encourage the adoption of cleaner and more efficient energy sources in rural areas.